A novel superhydrophobic surface based on low‐density polyethylene/ethylene‐propylene‐diene terpolymer thermoplastic vulcanizate. (1st August 2017) - Liu, Qingqing; Feng, Ruotao; Hua, Jing; Wang, Zhaobo
Abstract : A novel superhydrophobic surface based on low‐density polyethylene (LDPE)/ethylene‐propylene‐diene terpolymer (EPDM) thermoplastic vulcanizate (TPV) was successfully fabricated where the etched aluminum foil was used as template. The etched aluminum template, consisted of countless micropores and step‐like textures, was obtained by metallographic sandpaper sanding and the subsequent acid etching. The surface morphology and the hydrophobic properties of the molded TPV surface were researched by using field emission scanning electron microscope and contact angle meter, respectively. From the microstructure observation of the superhydrophobic LDPE/EPDM TPV surface, the step‐like textures obtained via molding with etched aluminum foil template and a large number of fiber‐like structures resulted from the plastic deformation of LDPE matrix could be found obviously. The obtained TPV surface exhibited remarkable superhydrophobicity, with a contact angle of 152.0° ± 0.7° and a sliding angle of 3.1° ± 0.8°.